Profiling SARS-CoV-2 HLA-I peptidome reveals T cell epitopes from out-of-frame ORFs - Weingarten-Gabbay, Shira; Klaeger, Susan; Sarkizova, Siranush; Pearlman, Leah R.; Chen, Da-Yuan; Gallagher, Kathleen M.E.; Bauer, Matthew R.; Taylor, Hannah B.; Dunn, W. Augustine; Tarr, Christina; Sidney, John; Rachimi, Suzanna; et al. (Cell, 2021)
T cell-mediated immunity plays an important role in controlling SARS-CoV-2 infection, but the repertoire of naturally processed and presented viral epitopes on class I human leukocyte antigen (HLA-I) remains uncharacterized. Here, we report the first HLA-I immunopeptidome of SARS-CoV-2 in two cell lines at different times post infection using mass spectrometry. We found HLA-I peptides derived not only from canonical open reading frames (ORFs) but also from internal out-of-frame ORFs in spike and nucleocapsid not captured by current vaccines. Some peptides from out-of-frame ORFs elicited T cell responses in a humanized mouse model and individuals with COVID-19 that exceeded responses to canonical peptides, including some of the strongest epitopes reported to date. Whole-proteome analysis of infected cells revealed that early expressed viral proteins contribute more to HLA-I presentation and immunogenicity. These biological insights, as well as the discovery of out-of-frame ORF epitopes, will facilitate selection of peptides for immune monitoring and vaccine development. [Display omitted] •Time course analysis of HLA-I immunopeptidome in SARS-CoV-2-infected cells•25% of detected HLA-I peptides originated from out-of-frame ORFs in S and N•Some out-of-frame peptides elicited stronger T cell responses than canonical peptides•Early expressed viral proteins dominated HLA-I presentation and immunogenicity Analysis of the HLA-I peptidome of SARS-CoV-2 infection identifies peptides derived from canonical and out-of-frame ORFs in viral S and N protein that are not captured by current vaccines and yield potent T cell responses in a mouse model as well as individuals with COVID-19.